Mycetoma: A local experience - Faqir, Farah; Rahman, Aziz ur (Journal of Postgraduate Medical Institute, 2011)
To report the existence of cases of mycetoma in our setup so that treatemnt can be specified. Clinically suspected mycetoma cases from January 1998 to December 2002 were analysed by various stains to differentiate between actinomycetes and eumycetoma. Mycetoma must be distinguished from chronic granulomatous disese and at the same time actinomycetes must be differentiated from dumycetoma as in all cases the treatent differs radically.